The Burden of a Highly Targeted Alert - Clarke, Tatyan; Kotarski, Tyler; Tobias, Marc (Applied Clinical Informatics, 2025)
Interruptive alerts in clinical decision support (CDS) systems are intended to guide clinicians in making informed decisions and adhering to best practices. However, these alerts can often become a source of frustration, contributing to alert fatigue and clinician burnout. Traditionally, an alert's burden is often assessed by evaluating the total number of times it is seen by end-users, which can overlook the true impact of highly interruptive workflows. This study demonstrates how an alert burden metric was employed to pinpoint an ineffective and burdensome alert, ultimately leading to its deactivation.This study aimed to evaluate the effectiveness of a burden metric in identifying high-impact, low-value alerts and prioritizing improvement efforts for a CDS governance team.A clinical informatics team employed Phrase Health's “Phrase Burden Index” (PBI) to assess alert burden and identify areas requiring intervention within the alert library.The team used the PBI to identify a breast cancer survivorship alert that fired 3,550 times in 2023, with the desired alert action chosen in only 0.00056% of alert firings. An investigation identified that this alert targeted a single clinician over the span of several years, and the CDS governance team promptly decommissioned the alert.This case highlights the value of continuous CDS monitoring, effective governance, and advanced analytics to identify and mitigate alert fatigue. Insights from this failure provide guidance for enhancing future CDS design, evaluation, and clinician engagement.
Keywords: clinical decision support; burden; alert fatigue; electronic health records; governance